DAMPAK PEMBELAJARAN ADAPTIF BERBASIS GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Hendrice Ramda, Apolonia; Arsenius Sudirahman; Tamur, Maximus (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2024)
The ability to understand concepts is one of the determinants of success in learning mathematics, so it must be possessed by students. The aim of this research is to determine the effect of implementing GeoGebra-based adaptive learning on the ability to understand mathematical concepts. This research uses a quantitative approach with a quasi-experimental type using a posttest-only control group design. The research population was class X students of Santu Petrus Informatics Vocational School, Ruteng. The samples were chosen randomly so that class X TKJ 1 was obtained as the experimental class and class X TKJ 5 as the control class. Data collection was carried out using the test method. Data analysis uses the t-test by first carrying out prerequisite test, namely normality and homogeneity. The significance level used is 5%. The results of the research show that GeoGebra-based adaptive learning has a significant influence on the concept understanding of class X students at the school. For this reason, it is recommended that mathematics teachers can utilize technology such as GeoGebra to improve students’ understanding of concepts in other materials.